2007
DOI: 10.1016/j.neuropsychologia.2007.05.023
|View full text |Cite
|
Sign up to set email alerts
|

The human medial temporal lobe processes online representations of complex objects

Abstract: There has been considerable debate as to whether structures in the medial temporal lobe (MTL) support both memory and perception, in particular whether the perirhinal cortex may be involved in the perceptual discrimination of complex objects with a large number of overlapping features. Similar experiments testing the discrimination of blended images have obtained contradictory findings, and it remains possible that reported deficits in object perception are due to subtle learning in controls, but not patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
324
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(353 citation statements)
references
References 58 publications
27
324
1
1
Order By: Relevance
“…Interestingly, the performance of MTL-damaged patients deviated from control performance in two ways: first, they reported seeing the Familiar Configurations as figure somewhat less often than controls, and second, they reported seeing the Part-Rearranged Novel Configurations as figure more often than controls. Taken alone, the first finding is consistent with the theoretical view that the PRC of the MTL contains representations of complex configurations Lee et al, 2005;Barense et al, 2005Barense et al, , 2007Barense et al, , 2010a; Bartko et al, 2007;Lee and Rudebeck, 2010;Burke et al, 2011), and damage to these configural representations removes effects of configuration familiarity on figure assignment. Taken together, however, the two findings suggest that either output from the PRC is privileged over that from lower-level visual regions during figure-ground assignment (a feedforward explanation for the data) or that the intact PRC plays a role in modulating processing in lower-level visual areas (a feedback explanation).…”
Section: Introductionsupporting
confidence: 80%
“…Interestingly, the performance of MTL-damaged patients deviated from control performance in two ways: first, they reported seeing the Familiar Configurations as figure somewhat less often than controls, and second, they reported seeing the Part-Rearranged Novel Configurations as figure more often than controls. Taken alone, the first finding is consistent with the theoretical view that the PRC of the MTL contains representations of complex configurations Lee et al, 2005;Barense et al, 2005Barense et al, , 2007Barense et al, , 2010a; Bartko et al, 2007;Lee and Rudebeck, 2010;Burke et al, 2011), and damage to these configural representations removes effects of configuration familiarity on figure assignment. Taken together, however, the two findings suggest that either output from the PRC is privileged over that from lower-level visual regions during figure-ground assignment (a feedforward explanation for the data) or that the intact PRC plays a role in modulating processing in lower-level visual areas (a feedback explanation).…”
Section: Introductionsupporting
confidence: 80%
“…Materials. The Fribbles used in this study are abstract and unconventional stimuli that consist of a body and four different appendages (Barense, Gaffan, & Graham, 2007). They have been described as non-nameable due to their complex yet novel appearance (Hartshorne, 2008) Each condition included 18 "same" trials and 18 "different" trials, and stimuli from the full range of Fribble species were included (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The finding was that patients with MTL lesions that included perirhinal cortex were intact in the minimum ambiguity condition and impaired in the intermediate and maximum ambiguity conditions. This result was interpreted to reflect a qualitative difference between the minimum condition (where only single features were relevant to the oddity discrimination) and the other two conditions (where conjunctions of features were relevant) (Barense et al 2007;Graham et al 2010). …”
Section: Visual Discrimination Tasksmentioning
confidence: 96%
“…Recent findings in monkeys and in humans with perirhinal cortex lesions have been taken to indicate that perirhinal cortex is needed for visual discrimination tasks when the test items have a high degree of feature ambiguity (Bussey et al 2002;Barense et al 2005Barense et al , 2007Lee et al 2005a,b; but see Clark et al 2011). It has also been suggested that the hippocampus is needed when spatial processing is required, for example, in visual discriminations involving scenes (Lee et al 2005a;Graham et al 2006).…”
Section: Visual Discrimination Tasksmentioning
confidence: 99%
See 1 more Smart Citation